Identificação de raças do nematóide de cisto da soja [Heterodera glycines (Ichinohe)] a partir de populações de campo e isolados monocísticos e resistência de cultivares comerciais à raça 3 - Santana, Hamilton (2007)
The Cyst Nematode is one of the main soybean crop pathogens in the world levels. In Brazil, such nematode is spread throughout Brazilian regions in which soybean is grown and its damage for soybean crops is dependent on the infestation level on the field. In Paraná State, this species is widely distributed, and it has been reported in 11 counties in the western region. The physiological race determination in such species is fundamentally important for the recommendation of resistant soybean cultivars to H. glycines. This work aimed to study the genetic variability in H. glycines polycystic populations collected from infested areas, through the identification of physiological races in monocystic populations by tests in soybean differential plants. It was also aimed at testing the reaction of soybean commercial cultivars to H. glycines to race 3. Field population and monocystic isolates from H. glycines, collected in Cruz Alta (RS), Porto Mendes (PR) and Novo Horizonte (PR), were developed in CD 202 soybean plants. Soybean differentials and soybean commercial cultivars were seeded in tubes, inoculated in the V1 stage with 5.000 eggs and J2 and kept in a greenhouse under temperature ranging from 28 to 30oC. The greenhouse essays followed a completely randomized design with seven replications. The physiological race identification was carried out with two field populations and nine monocystic isolates whereas the resistance test was developed on 18 commercial cultivars. The evaluation procedure was accomplished at 28 days apart the inoculation and based on the Parasitism Index (PI). The PI was calculated on the number of females and cysts found on the differentials and the cultivars tested in relation to the check cultivar LEE . The tests in differential plants with monocystic isolates revealed the presence of the races 2, 5 and 6 to Porto Mendes, 3 and 6 to Cruz Alta and 5 and 6 to Novo Horizonte. Field populations showed the presence of race 6 in Porto Mendes and race 3 in Cruz Alta. Most of commercial cultivars tested were resistant to H. glycines race 3 while the cv. Liderança and the CD 217 presented susceptibility. The results showed that the race identification from monocystic isolates assists in the identification of genetic variability in field populations of H. glycines, what is not possible according to the race scheme based in polycystic populations extracted from the soybean crop fields